Kurdish Scholarly Networks and the Making of Indonesian Islamic Orthodoxy: Textual Transmission, Epistemological Negotiation, and Sunni Intellectual Formation - Zulkifli, Zulkifli; Fahri, Muhamad; Suwaidi, Ahmad (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2026)
Islamic orthodoxy in Indonesia has been substantially shaped by the transregional transmission of scholarly texts produced outside the Arab core. This study examines how the works of five Kurdish ulama, namely Ibrāhīm al-Kūrānī, Ja‘far al-Barzanjī, Muḥammad b. Sulaymān al-Kurdī, Muḥammad Amīn al-Kurdī, and Bediuzzaman Said Nursi were transmitted to and appropriated within the Indonesian Muslim context. Employing a historical-anthropological and literature approach, this study traces the intellectual networks connecting these scholars to Jawi students through the Haramayn and Cairo as primary nodes of scholarly exchange. The findings demonstrate that Kurdish scholarly texts were not received passively; rather, they underwent active epistemological negotiation through philological practices including ḥāshiya, sharḥ, and interlinear translation across manuscript, print, and digital periods. This transmission reinforced the Ash‘ari-Shāfi‘ī-Sufi synthesis that defines Indonesian Sunni orthodoxy, while enabling adaptation into local devotional rituals and ethical literacy movements. Theoretically, this study challenges the center-periphery model in global Islamic studies by repositioning the Kurdish scholarly tradition as an autonomous and productive transregional axis in the intellectual formation of Indonesian Islam.